Pelatihan Pembelajaran Tematik Pada Sekolah Menengah Pertama Menggunakan Kolaborasi Pendekatan Teaching At The Right Level (TARL) Dan Model Problem Based Learning (PBL) - Puspananda, Dian Ratna; Cuhanazriansyah, Muhammad Rinov; Amir, Day Ramadhani; Puspitaningsih, Siska; Rohman, Nur; Zetia Ramadani, Salsabila (Universitas Garut, 2024)
This research explores the potential improvement of thematic learning quality in Junior High School (JHS) through the collaboration of the Teaching at the Right Level (TaRL) approach and the Problem-Based Learning (PBL) model. TaRL is employed to identify students' understanding levels of specific concepts within the thematic curriculum, while PBL is utilized to design challenging and real-world relevant learning activities. The collaboration aims to personalize learning, develop high-order thinking skills, and enhance student motivation and engagement.